Pengaruh Jenis Pakan Berbeda terhadap Warna dan Pertumbuhan Berat Benih Ikan Cupang di Bak Pemeliharaan - Irma Yunitasari; Indra Wirawan; Maria Agustini (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
One of the problems of cultivating Betta fish (Betta sp.) which can hamper this cultivation effort is the slow weight growth of the fish. The aim of this research is to determine the effect of providing different types of feed on the growth in weight and color of Betta fish (Betta sp.) size 1- 1.5 in the maintenance tank. The research containers used 27 used gallons with a capacity of 15 liters and each research container was filled with fresh water with a volume of 10 liters. The test animals used were Betta fish seeds measuring 1–1.5 cm. This research used an experimental method using an experimental design in the form of a Completely Randomized Design (CRD) with 3 treatments and 9 repetitions to obtain 27 trials. Other parameters that are also studied include water quality including water temperature ranged from 26,1 – 29 ̊C and pH (degree of acidity) ranged from 7 - 8.